Real options and the jorgensonian user cost of capital - Óscar Gutiérrez (Investigaciones Económicas, 2005)
Dixit and Pindyck (1994) claim that the Jorgensonian rule of investment(Jorgenson, 1963) does not hold in uncertain settings. This note shows thatthe validity of that claim depends crucially on the particular process chosento describe the economic uncertainty. In fact, the Jorgensonian rule of investmentholds in other real options models.